Kegiatan Imunisasi Dasar Di Desa Purba Lama Kecamatan Lembah Sorik Merapi Kabupaten Mandailing Natal - Rahayu Tinendung, Dewi Sri (Jurnal Masyarakat Indonesia (Jumas), 2022)
The high infant and toddler mortality rate in Indonesia causes a decline in public health. This problem reflects the need for Government participation at the national level to support and maintain supervision of the immunization program in Indonesia. This activity aims to increase the knowledge of mothers and the community. The methods used in this activity were lectures, discussions and questions and answers. This activity was carried out because there are still many people who do not understand complete basic immunization. Participants already understand and understand complete basic immunization